Electricity system in Jordan: Status & prospects. (January 2018) - Al-omary, Murad; Kaltschmitt, Martin; Becker, Christian
Abstract: The Kingdom of Jordan, like other countries, faces considerable challenges to cover always and securely the given electricity demand. This is due to e.g. limited locally available fossil fuel resources, insufficient available conversion capacities and the financial weakness of the energy entities. Additionally, the electricity demand is strongly rising due to increasing industrialization and a fast growing population; the latter is also true due to refugees from Syria and Iraq. One option to contribute to a secured and a climatic sound improved electricity generation system is an increased use of renewable sources of energy. For Jordan, this is especially true due to the availability of favourable solar and wind resources. Against this background, this paper assesses the current status of the electricity sector in Jordan and discusses the possible future role of renewable sources of energy for electricity generation within the Jordanian electricity system. The investigation shows that electricity from wind and solar can contribute indeed considerably to a more secure and climatic sound electricity supply system. Thus the realization of an exploitation strategy to increase the share of electricity from wind and solar could clearly be beneficial for the Kingdom of Jordan.